Servitization for Teaching and Research Laboratories: Guidelines for a New Business Model Driven by Practical Use Cases - Reverberi, Davide; Esposito, Giovanni; Romagnoli, Giovanni (International Journal of Online and Biomedical Engineering (iJOE), 2022)
In this paper, we present a pattern for assessing the feasibility of laboratories and lab networks to operate in a service-oriented form of business. Our focus is on the field of engineering, and on a network of academic labs, and we aim to provide a practical tool for disclosing the opportunity of servitization, or to use Laboratories-as-a-Service (LaaS), for interested companies. By using a traditional pitch deck approach, we define the available digital online offer of the specific labs, and we structure a questionnaire to investigate the market demand. Afterwards, we sketch the main servitization characteristics required to digital online labs from a business perspective. The pattern we propose has been used as a guideline for interviews to selected stakeholders of two specific labs, namely a remotely available RFID lab for internal logistics in the retail sector, and a serious game for operations and supply chain management. The answers we collected suggested the feasibility of the labs servitization, by defining both strengths and weaknesses.